P170 TB-HIV co-infection: how does the UK compare to Europe?. (16th November 2010) - Kruijshaar, M E; Pimpin, L; Ködmön, C; Lipman, M; Delpech, V; Rice, B; Drumright, L; Manissero, D; Abubakar, I
Abstract : Background: Tuberculosis (TB) and HIV/AIDS are global public health problems with considerable mutual interaction. Data on national TB-HIV co-infection trends are essential to plan and evaluate TB-HIV control measures. We compared the burden of co-infection and how this is monitored in surveillance systems in England with the rest of Europe. Methods: A systematic search of academic and grey literature identifying studies reporting data on TB-HIV co-infection in EU/EEA countries. A questionnaire survey among EU/EEA countries' TB surveillance leads, regarding surveillance methods, data and proportion of cases tested for HIV. For England, Wales and Northern Ireland, cases reported to Enhanced Tuberculosis Surveillance matched to national HIV/AIDS case reports. Results: A total of 55 papers were identified providing estimates on the proportion of TB patients co-infected with HIV. From 30 EU/EEA countries 25 TB questionnaires were returned. This gave prevalence data for 23 countries. In England, the prevalence of HIV co-infection among TB patients rose from 5% in 2000 to 8% in 2005, with a peak at 9% in 2003–2004. These figures are at the higher end of what is observed in Europe. France, Iceland and Portugal (11–15%) had higher co-infection levels, while similar levels were found for Estonia and Malta (9%). Very low levels were reported from central European countries (0–1%). A rise in co-infection levels was seen in Estonia, Latvia, Lithuania, the UK and Belgium, while decreases were seen in Spain and Portugal. The burden was higher in countries reporting high levels of HIV testing and countries with a higher HIV burden. Information on TB patients' HIV status was collected in 19/25 TB surveillance systems responding to the survey. While 17 countries rely on clinician reporting, in England and Finland, data are obtained by matching to national HIV/AIDS surveillance data due to confidentiality concerns. Conclusion: Levels of TB-HIV co-infection vary widely across EU countries, with the UK being at the higher end. Our data suggest that TB-HIV surveillance appears patchy and needs strengthening to better inform control policies and clinical practice.